Prophylactic use of tranexamic acid for prevention of bleeding during transbronchial lung biopsies - A randomized, double-blind, placebo-controlled trial. (November 2020) - Kuint, Rottem; Levy, Liran; Cohen Goichman, Polina; Huszti, Ella; Abu Rmeileh, Ayman; Shriki, Ora; Abutbul, Avraham; Fridlender, Zvi G.; Berkman, Neville
Abstract: Background: Although massive bleeding following transbronchial lung biopsies (TBLB) is rare, even minor hemorrhage may prolong the procedure and result in inadequate sampling. Tranexamic acid (TXA) is an antifibrinolytic agent, which reduces bleeding in numerous scenarios, however, its prophylactic use in mitigating post-TBLB bleeding has not been investigated. We conducted a prospective, randomized, double-blind, placebo-controlled trial to determine whether topical infusion of TXA prior to TBLB would reduce bleeding, shorten procedure duration and increase the number of biopsies obtained. Methods: We blindly randomized patients undergoing TBLB to receive topical TXA or placebo in the lobar bronchus prior to biopsies. Vital signs, procedure length, fluid balance (as a measure of the amount of bleeding), operator's assessment of bleeding, and number of biopsies obtained were measured. Data was analyzed using the two-tailed Student's T-Test, Chi-square or Mann-Whitney tests as appropriate. Results: Fifty patients were randomized, 26 to the TXA arm. The bleeding in the TXA group was significantly lower ( P  = 0.0037), with more specimens being obtained (placebo 7 (6, 9) (median and interquartile range) vs. TXA 9 (8, 10), P = 0.023) and no difference in procedure length (placebo 30 min (29.3, 34.3) vs. TXA 30 (24.8, 36), P = 0.90). There were no clinically significant adverse events in any of the groups up to one month of follow up. Conclusion: Endobronchial installation of TXA prior to obtaining TBLB results in less bleeding and allows more biopsies to be obtained with no additional adverse events. The prophylactic use of TXA during TBLB may be considered as standard. Highlights: Transbronchial biopsies often cause minor hemorrhage but this may deter operators from obtaining sufficient material. We blindly compared prophylactic topical instillation of TXA placebo prior to transbronchial lung biopsies to placebo. TXA resulted in less operator reported bleeding, and more specimens obtained during the procedure compared with placebo. This study may help change common practice during bronchoscopy.